2022
DOI: 10.1177/00405175221084277
|View full text |Cite
|
Sign up to set email alerts
|

Sound absorption coefficient analysis and verification of weft-knitted spacer fabrics for noise reduction application

Abstract: Weft-knitted spacer fabrics with robust sound absorption ability had great application prospects in noise control engineering, but the relationship between structural parameters and sound absorption still required to be investigated further. In this work, a series of wet knit spacer fabrics with different structural parameters were fabricated, and the measured and predicted sound absorption coefficients were also compared. The results showed that the airflow resistivity was mainly determined by their density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The results showed that the airflow resistivity was mainly determined by their density, thickness, porosity, and yarn arrangement. The sound absorption coefficient of samples can be enhanced with the increasing thickness and airflow resistivity, and the absorption tendency of double layer spacer fabrics assembled by samples with more yarns is coincident to those, and the coefficients were higher than 0.5 above 1000 Hz and higher than 0.8 above 2000 Hz.. [19]. Nazan et al developed a hybrif layerd structures base on natural fabric reinforces composites and warp knitted spacer for acoustic applications.…”
Section: Acoustic 3d Spacersmentioning
confidence: 99%
“…The results showed that the airflow resistivity was mainly determined by their density, thickness, porosity, and yarn arrangement. The sound absorption coefficient of samples can be enhanced with the increasing thickness and airflow resistivity, and the absorption tendency of double layer spacer fabrics assembled by samples with more yarns is coincident to those, and the coefficients were higher than 0.5 above 1000 Hz and higher than 0.8 above 2000 Hz.. [19]. Nazan et al developed a hybrif layerd structures base on natural fabric reinforces composites and warp knitted spacer for acoustic applications.…”
Section: Acoustic 3d Spacersmentioning
confidence: 99%
“…In addition, the effect of such parameters as knit structure, thickness, and density of spacer fabrics on the sound absorption property have been investigated. [21][22][23][24] Hence the macroscale pores can also be regulated. To sum up, a controllable hierarchical pore structure within 3D spacer fabrics can be obtained.…”
mentioning
confidence: 99%